Marital satisfaction and therapeutic regimen compliance in hemodialysis patients in hospitals of Shahid Beheshti University of Medical Sciences and Health Services in 1388- 89. - Zoriasatein, Fereshteh; Hejazi, Sima Sadat; abedsaeedi, Zhila; Nassiri Oskuee, Navideh; yaghmaei, Farideh (Advances in Nursing & Midwifery, 2012)
Abstract Backgrounds and aim Therapeutic regimen non compliance is a common problem in hemodialysis patients. It is associated with many side effects. Marital satisfaction and conflictions in dyadic relationships have an important effect on compliance of a complex regimen. This study aims to determine the correlation between marital satisfaction and therapeutic regimen compliance in hemodialysis patients in hospitals of Shahid Beheshti University of Medical Sciences and Health Services in 1388-89. Materials and Methods In this descriptive correlatiional study 100 hemodialysis patients were selected through the judgmental sampling method. Data gathering tool was a questionnaire consisting three parts: demographic data, disease and ENRICH Marital Satisfaction Inventory. The latter part is validated by content validity method. The reliability of ENRICH Marital Satisfaction Inventory was determined by Chronbach’s = method. The questionnaires were completed by patients during hemodialysis. In order to determine the compliance of therapeutic regimen, the researcher recorded the mean of the last three months’ values of P, K, interdialytic weight gain, and the numbers of missed dialysis sessions using patient’s documents. Data were analyzed by SPSS statistical software Findings While 56% of patients had compliance in therapeutic regimen. 59% had low and very low and 41 % of patients had moderate and high marital satisfaction. There was a significant correlation between marital satisfaction and therapeutic regimen compliance and marital satisfaction in patients with therapeutic regimen compliance was high. Conclusion Planning for counseling and supportive programs concerning marital satisfaction can be beneficial for patients and their families in order to increase their therapeutic regimen compliance. Keywords: Marital satisfaction, Compliance, Hemodialysis, Chronic renal failure